Seafood choices : balancing benefits and risks - Nesheim, Malden C.; Yaktine, Ann L. (National Academies Press, 2007)
1. Introduction -- 2. Consumption patterns and composition of seafood -- 3. Health benefits associated with nutrients in seafood -- 4. Health risks associated with seafood consumption -- 5. Analysis of the balancing of benefits and risks of seafood consumption -- 6. Understanding consumer decision making as the basis for the design of consumer guidance -- 7. Balancing choices : supporting consumer seafood consumption decisions -- Appendixes -- A. Glossary and supplementary information -- B. Data tables -- C. Tables and scenarios -- D. Open session and workshop agendas -- E. Committee member biographical sketches.